Access for cataract surgery in diabetes. A qualitative study with a managerial approach - Hormigó Puertas, Iraisi; Arocha Maríño , Carmen; Avalos-García, María Isabel; Castillo Arocha , Antoine; Hormigó Tablada , Katerine (Horizonte Sanitario, 2023)
Objective: To explore the gaps that exist for access to cataract surgery in people with type 2 diabetes.Materials and methods: a qualitative research of a phenomenological type with a managerial approach was carried out. Management tools and techniques by health processes and Lean-health methodology were used. The field work was carried out in the municipalities of La Lisa, Marianao and Playa where the experiences and expectations of 46 patients were explored in six discussion groups, the criteria of nine family doctors and six ophthalmologists from the primary health level were obtained, in two discussion groups.Results: The experiences of patients, family doctors and ophthalmologists, organized by categories (diagnosis, continuity and communication, social support and workload) have in their content the gaps present in the care processConclusion: The gaps identified in this study are sufficient to explain why many patients do not access cataract surgery in a timely manner.Keywords: Gaps in health status; Mellitus diabetes; Cataract extraction; Evaluation study.